Transcranial Doppler screening for stroke risk in children with sickle cell disease: a systematic review. - Mazzucco, S; Diomedi, M; Qureshi, A; Sainati, L; Padayachee, T (SAGE Publications, 2017)
Background: Sickle Cell Disease (SCD) is one of the most common causes of stroke in children worldwide. Based on the results of the Stroke Prevention Trial in Sickle Cell Anaemia (STOP), annual Transcranial Doppler Ultrasound (TCD) screening for affected children is standard practice. However, the need for TCD surveillance programmes could override the accuracy of the screening, affecting the correct stratification of stroke risk and subsequent clinical management of the target population. Aims: To shed light on this issue, a systematic review of the literature on TCD screening for children and adolescents with SCD was carried out (CRD42016050549), according to a list of clinically relevant questions, with a particular focus on screening practices in European countries. Quality of the evidence was rated using GRADE. Summary of review: Thirty-three studies published in English or French were included (5 randomised controlled trials, 8 experimental non-randomised and 20 observational studies). The quality of the retrieved evidence ranged between low and high, but was rated as moderate or high most of the times. TCD is effective as a screening tool for primary prevention of stroke in SCD children. There is no high quality evidence on the effectiveness of alternative screening methods, such as imaging-TCD (TCDi) with or without angle correction or magnetic resonance angiography (MRA). No evidence was found on effectiveness of the screening on children on hydroxyurea and with genotypes other than HbSS and HbS/β0. No European data were found on screening rates or adherence of screening practices to the STOP protocol. Conclusions: High quality studies on alternative screening methods that are currently used in real-world practice, and on screening applicability to specific subgroups of patients are urgently needed. Considering the low awareness of the disease in European countries and the lack of data on screening practices and adherence, clinicians need up-to-date guidelines for more uniform and evidence-based surveillance of children with SCD.